A novel cell therapy for stress urinary incontinence, short‐term outcome123. Issue 4 (12th September 2012) - Shirvan, Maliheh Keshvari; Alamdari, Daryoush Hamidi; Mahboub, Mohammadreza Darabi; Ghanadi, Alireza; Rahimi, Hamid Reza; Seifalian, Alexander M.
Abstract Aims The aim of this study was the safety assessment of urethra injections of autologous total nucleated cells (TNCs) along with platelets, which focused on the outcome over a 6 month period. Methods An open, prospective study was conducted on 9 patients with severe stress urinary incontinence (SUI). At the baseline, 1, 3, and 6 months after external urethral sphincteric and submucosal injections of autologous TNCs along with platelets, the patients were assessed according to cough tests, Q‐Tip tests, urodynamics, 1 hr pad tests, upper tract ultrasonography (UTU), post voiding residue (PVR), International Consultation on Incontinence Questionnaire‐Urinary incontinence (ICIQ‐UI), and International Consultation on Incontinence Modular Questionnaire‐Quality of Life (ICIQ‐QOL). On the 3rd month post‐injection, the maximum urethral closure pressure (MUCP) and abdominal leak point pressure (ALPP) were measured in one patient with intrinsic sphincteric deficiency (ISD; the baseline: ALPP < 60 and MUCP < 30 cmH2O). Results No complications were observed after injection. At 6‐months' follow up (F/U), all the patients considered themselves clinically cured with eight women completely continent and one marked improvement. Mean age was 48.9 ± 13.8 years. Before the injection, urodynamics, UTU, and PVR were normal and cough tests, 1 hr pad tests were positive in patients. At 1, 3, and 6 months post‐injection, there was a significant improvement in ICIQ‐UI, ICIQ‐QOL (P < 0.05). UTU and PVR were normal, cough tests, and 1 hr pad tests were negative, except for ISD patient with severe coughs (at month 3: ALPP = 92 and MUCP > 30 cmH2O). Conclusion Cell therapy consisting of intrasphincteric and submucosal injections of autologous TNCs along with platelets in SUI patients is a feasible and safe procedure. The results point out those subjects cured or with marked improvement after 6 months F/U. Neurourol. Urodynam. 32: 377–382, 2013. © 2012 Wiley Periodicals, Inc.